Fundamentals of spatial analysis and modelling - Gao, Jay (Boca Raton : CRC Press, 2022)
'This textbook provides comprehensive and in-depth explanations of all topics related to spatial analysis and spatiotemporal simulation, including how spatial data are acquired, represented digitally, and spatially aggregated. Also features the nature of space and how it is measured. Descriptive and inferential analyses are covered for point, line, and area data. It captures the latest developments in spatiotemporal simulation with cellular automata and agent-based modelling, and through practical examples discusses how spatial analysis and modelling can be implemented in different computing platforms. A much-needed textbook for a course at upper undergraduate and postgraduate levels'--
Space in spatial analysis -- Spatial data and association -- Descriptive and inferential spatial analysis -- Geostatistics and spatial interpolation -- Spatial modelling -- Spatial simulation -- Time-explicit spatial analysis and modelling.
OCLC-licensed vendor bibliographic record.
Keywords: Spatial analysis (Statistics); Spatial analysis (Statistics) -- Mathematical models; Geology -- Statistical methods -- Data processing